Framing climate change as a human health issue: enough to tip the scale in climate policy?. Issue 8 (August 2021) - Rossa-Roccor, Verena; Giang, Amanda; Kershaw, Paul
Summary: Almost four decades of climate science have not yet led to transformative policy change at the pace and scale required to confront the climate crisis. Colleagues in the planetary health community attribute much potential to framing climate change as human health issue in order to create greater impact on policy makers. In this Personal View, we discuss the promise and limitations of this approach by drawing on insights from political science and public policy with regards to the complexity of these contentious policy issues. We argue that we, as academics, have a moral obligation to embrace an active role in the knowledge-to-action (KTA) sphere and that we would be well advised to expand our KTA approach to include evidence-based strategies, such as lobbying or civil resistance. As scientists, we can no longer wait to embrace the realpolitik insights of political science to move our evidence into policy action.